Psychometric Properties of the Elementary Social Behavior Assessment in Swedish Primary School: A Teacher Rated Index of Students’ Prosocial School Behaviors - Wikman, Carina; Allodi, Mara Westling; Ferrer-Wreder, Laura (Frontiers in Education, 2021)
This study examined the psychometric properties of a Swedish language adaption of the teacher-rated Elementary Social Behavior Assessment (ESBA), which provides an index of students’ prosocial school behaviors. Participants were eight teachers (two teachers per school in four schools) who rated their students (N = 143 children, M age = 8 years old). The ESBA factor structure was tested with Confirmatory Factor Analysis in a series of models. The two- and three-factor models showed better fit. ESBA showed high internal consistency at the observed level. ESBA’s psychometric properties show initial promise as a tool to help Swedish teachers to support students’ prosocial skills development.